Pendampingan Penguatan Green Economy melalui Peningkatan Kualitas Karakter Kewirausahaan Pengusaha Kuliner di Foodcourt Universitas Negeri Yogyakarta - Lilia Pacsa Riani; Yuni Mariani Manik; Endang Mulyani; Supriyanto; Sri Sumarsih (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2025)
ABSTRACT This Community Service (PKM) activity aims to strengthen the implementation of a green economy among culinary entrepreneurs at the Yogyakarta State University (UNY) Food Court by enhancing their green entrepreneurial character. The approach used included counseling, training, participatory discussions, and mentoring, involving 27 tenants from several culinary areas on campus. The main focus of the activity was to build awareness of the importance of environmentally friendly business practices, develop sustainable product innovations, and improve waste management and recycling. The results of the activity showed a significant increase in participants' understanding of the concept of green entrepreneurship; 85% of tenants expressed a commitment to reducing single-use plastics and implementing environmentally friendly product innovations. In addition, a collaboration with the campus waste bank and a written commitment to implementing a circular economy were established. This program contributes to UNY's vision as a green campus and serves as a model for implementing a green economy in the culinary MSME sector. Keywords: green economy, green entrepreneurship, culinary MSMEs, circular economy, community service   ABSTRAK Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk memperkuat penerapan green economy di kalangan pengusaha kuliner Foodcourt Universitas Negeri Yogyakarta (UNY) melalui peningkatan karakter kewirausahaan hijau. Pendekatan yang digunakan meliputi penyuluhan, pelatihan, diskusi partisipatif, dan pendampingan dengan melibatkan 27 tenant dari beberapa area kuliner kampus. Fokus utama kegiatan adalah membangun kesadaran akan pentingnya praktik bisnis ramah lingkungan, mengembangkan inovasi produk berkelanjutan, serta meningkatkan manajemen limbah dan daur ulang. Hasil kegiatan menunjukkan peningkatan signifikan dalam pemahaman peserta terhadap konsep green entrepreneurship; 85% tenant menyatakan komitmen mengurangi plastik sekali pakai dan menerapkan inovasi produk ramah lingkungan. Selain itu, terbentuk kerja sama dengan bank sampah kampus dan komitmen tertulis penerapan ekonomi sirkular. Program ini berkontribusi terhadap visi UNY sebagai green campus dan menjadi model penerapan green economy di sektor UMKM kuliner. Kata Kunci: green economy, kewirausahaan hijau, UMKM kuliner, ekonomi sirkular, pengabdian masyarakat